A Move-Step Analysis of Inter-University Agreements - Calviño Ruiz, Karen (Universidad Central "Marta Abreu" de Las Villas, 2013)
Inter–University Agreements (IUAs) are legal documents designed for achieving cooperatio among universities. In Cuba, International Relations Officers and translators are the ones responsable for writing or translating these agreements which are mainly prepared in Spanish and English. In spite of the significance of these documents, they might not be as effective as they are meant to be, especially when written in English. This is mainly due to the fact that these agreements use specific lexis , structures and style typical of the legal document style. The purpose of this thesis is to describe the linguistic and comunicative characteristics of IUAs in terms of moves and steps. As a result of this study, its author proposes three diversified intercultural models that Cuban international officers and translators could follow when preparing or translating an IUA into English. From a linguistic point of view, This thesis makes a contribution to the study of specialized texts (mainly legal, business and diplomatic). It is also hoped that this study will increase the competence of Cuban experts, professors and staff when communicating with forign institutions, especially those who had adopted English as their lingua franca . The methodology proposed in this thesis, could apply not only to afficial academic documents but to any other document related to the fields of legal, diplomatic or business comunication.
Keywords: Inter University Agreements; Legal Documents; International Relations Officers; Legal Comunication; Diplomatic Comunication; Bussines Comunication; Comunicación; Diplomatic Comunication; International Relations Officers; Bussines Comunication; Inter University Agreements